A multidisciplinary approach to insanity assessment as a way to reduce cognitive biases. (February 2021) - Scarpazza, Cristina; Zampieri, Ilaria; Miolla, Alessio; Melis, Giulia; Pietrini, Pietro; Sartori, Giuseppe
Highlights: Reliability of insanity assessment is low due to intrinsic limitation of psychiatric evaluation and cognitive biases. Strategies to improve the reliability of insanity evaluation are strongly needed. Classical insanity assessment do not incorporate neuroscientific evidences Multidisciplinary assessment and convergence of evidences have been proposed as a way to increase inter-subject concordance This approach will minimize the impact of cognitive bias on insanity opinion. Abstract: Insanity assessment requires the evaluation of the psychopathological condition that underlies the mens rea . Psychopathological evaluation may be quite challenging due to (i) absence of biomarkers; (ii) low inter-rater reliability; (iii) presence of cognitive bias. This intrinsic low reliability of forensic psychiatric diagnosis does impact on insanity assessment, leading to arbitrary and unjust legal outcomes for the examinee. Thus, strategies to improve the reliability of insanity evaluation are strongly needed. A multidisciplinary approach has been proposed as a way to enrich clinical diagnosis with reliable and biologically founded data, thus minimizing subjectivity, reducing controversies and increasing inter-subject concordance in insanity assessment. By discussing a real case, here we show how the convergence of multiple indices can produce evidence that cannot be denied without introducing logical fallacies. Applying this approach, the forensic discussion will move from the presence/absence of psychopathology to the impact of psychopathology on insanity. This article illustrates how a multidisciplinary evaluation, which integrates neuroscientific methods with the classical insanity assessment, may lead to a more accurate approach in insanity evaluation. Critically, this approach will minimize the impact of cognitive bias on insanity opinion and thus result in an improvement of the whole criminal justice process.